Pelatihan Penyusunan Bahan Ajar Online Interaktif Untuk Meningkatkan Kompetensi Profesional Guru MA Al-Munawwaroh Merauke - Reski, Andi; Bawawa, Marni (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
21st century learning is about learning that integrates literacy skills, learning knowledge, and skills in mastering technology. Regarding the abilities, games and skills of the teacher, of course, in this case, we talk about competence. One of the most important competencies possessed by a teacher so that the learning process can run smoothly and optimally is professional competence. Therefore, the purpose of the Community Partnership Service activities carried out at MA Al-Munawwaro Merauke is to improve the professional competence of teachers. This activity is carried out in three forms, namely socialization, training and mentoring, and evaluation. The activity stages are in the form of socializing the use of Microsoft PowerPoint in the preparation of online teaching materials, training and assistance in the preparation of online teaching materials with Microsoft PowerPoint, as well as evaluating activities to determine the increase in the professional competence of MA Al-Munawwaro Merauke teachers. Indicators of increasing competence are marked by the ability of teachers to develop materials creatively and also the ability of teachers to utilize information and communication technology to produce interactive online teaching materials.